How do dinosaurs eat their food? - Yolen, Jane.; Teague, Mark (New York : Blue Sky Press, 2005)
Presents an introduction to table manners, in simple text with illustrations, explaining proper etiquette as a variety of dinosaurs display playful antics at the dinner table.
Horn Book Starred.
Publisher's Weekly.
School Library Journal.
1.9
K-3
Keywords: Dinosaurs -- Juvenile fiction; Table etiquette -- Juvenile fiction; Dinosaurs -- Fiction; Etiquette -- Fiction; Stories in rhyme; Table etiquette -- Fiction; Dinosaurs -- Fiction; Etiquette -- Fiction; Stories in rhyme; Table etiquette -- Fiction